United States : Publication of Financial Sector Assessment Program Documentation; Technical Note on Selected Issues on Oversight of Payment. (IMF Staff Country Reports; Country Report ;, 2010)
This technical note reviews the United States Federal Reserve's oversight of payment, clearing, and settlement systems. As is typical for central banks, the Federal Reserve plays multiple and important roles in payment and settlement systems. The Federal Reserve also exercises supervisory and regulatory responsibility over certain private-sector payment and settlement systems that have bank charters subject to Federal Reserve supervision or that fall under relevant supervisory provisions for bank service companies.